Empowering Undergraduate Nursing Students Against Workplace Violence - Keirstin E. Uomoto; Ayman Tailakh; Elizabeth J. Winokur (Nursing Education Perspectives, 2026)
Workplace violence (WPV) in health care is a growing and urgent concern, significantly impacting both nurses and nursing students. This quasi-experimental study evaluated a structured, trauma-informed WPV training program designed to enhance behavioral health care competency in undergraduate nursing students. Statistically significant improvements were observed in overall behavioral health care competency scores ( p = .045, Cohen’s d = 0.32), with particularly pronounced gains among accelerated baccalaureate students. These findings underscore the importance of integrating comprehensive WPV training into nursing curricula to better prepare students for the realities of clinical practice.